Byrne_et_al_Mako_Tagging_Fate_data - Byrne, Michael; Cortes, Enric; Vaudo, Jeremy; Harvey, Guy; Sampson, Mark; Wetherbee, Bradley; Shivji, Mahmood (Dryad Digital Repository, 2017)
Tagging information and ultimate fate of all mako sharks in this study.Can be used to recreate survival analysis